The developmental policy of halal product guarantee in the paradigm of maqāṣid sharī`ah in Indonesia - Agus Waluyo (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
The guarantee of halal products that meet the quality, hygiene, health and safety standards has become a primary need for every person to protect religion and soul. This study aims to elaborate government policies related to regulations in supporting the development of halal industry and its barriers to implement halal product guarantee. In addition, this study also tries to reveal halal industrial development strategies. This article is qualitative research using library approach. The research findings show that to guarantee halal product in a systematic and comprehensive way for Indonesian society, the government has issued JPH Law which contains maqāṣid sharī`ah values. Besides, it is found difficulties in the process of obtaining halal certification faced by the producers. This study implies that it still needs rules from the government to support the implementation of JPH Law so that it can encourage the development of halal industry, which finally can establish Indonesia as the epicentre of the world sharia economy.